Potensi Usaha Budidaya Tanaman Wortel (Daucus carota L.) Di Rurukan Kota Tomohon - Rinondom AR Mogea; Vanny H Siwi Vanny H Siwi; rina mogea (FMIPA Universitas Papua, 2023)
Carrot business development provides a source of income to meet the needs of farming families and also to continue their farming activities. This study aims to analyze profits, Break Event Point values and the feasibility of carrot farming in Rurukan Village. he data collection method uses a survey method. The data used includes primary and secondary data taken by interview, observation and recording techniques. Determination of carrot farmer samples by purposive sampling with the consideration that farmers obtain credit from the banking sector with an average land area of 1 ha. The data analysis used is profit analysis namely Revenue/Cost (R/C), Break Even Point (BEP) and Internal Rate of Return (IRR). The results showed that the profit of each respondent in the first harvest season averaged IDR 1,210,745 and the profit of farmers in the second season was IDR 11,402,917. The first season's R/C value was 164 and the second season's R/C value was 300. The first season's BEP value was Rp. 331 and for the second harvest was 157. The BEP value of production volume for the first season was 21328 kg and for the second harvest was 12100 kg. The NPV value is IDR 266,090,644 and the IRR value is 60%. This value means that the carrot cultivation business in Rurukan Village is profitable and feasible to develop.